Cavitation-driven bubble evolution and load mechanisms in particle-wall multiphase interactions - Yuxuan Deng; Haiting Xi; Zhentao Gu; Xiaoming Yan (Ultrasonics Sonochemistry, 2025)
The interaction among cavitation bubbles, particles, and solid boundaries critically governs energy transfer in fluid systems. This study employs high-resolution numerical simulations to investigate how fluid flow and solid surfaces influence small scale bubble dynamics, energy dissipation, and load effects. The simulations cover a range of initial particle-bubble distances (Dp = 0.5 to 1.2) and sinking velocities (vp = 0.3 to 1.8), revealing how particle motion and boundary proximity influence bubble evolution and pressure loading. Results indicate that a single particle exposed to bubble collapse experiences intense water-jet impacts, producing unimodal pressure peaks exceeding 40 MPa. In contrast, near-wall scenarios generate bimodal pressure responses caused by bubble rupture and micro-jet formation, which concentrate collapse energy onto the particle; the secondary peak reaches approximately 20 MPa. At higher sinking velocities, particles penetrate the bubble, releasing energy as acoustic radiation and triggering complex oscillations. Although residual flow and pressure gradients continue to drive bubble shrinkage, jet formation is suppressed. Particle-bubble interactions modulate collapse behavior and attenuate water-jet loading on nearby solid boundaries. At lower velocities, delayed liquid film formation further reduces energy dissipation. These findings elucidate how boundary conditions and particle kinematics shape cavitation-induced energy transfer, offering insights into fluid–structure interactions relevant to acoustic erosion and sonochemical processes.